2011
DOI: 10.1519/jsc.0b013e3181ecd072
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Correlates of Skating Performance in Women's and Men's Ice Hockey

Abstract: In the present study the relationship between the off-ice and onice performance as well as the relation to body weight and body composition was investigated in women and men playing ice hockey on a comparable competitive level. Method: Eleven female, 24+3.0 years and ten male ice hockey players, 23+2.4 years were tested for background variables: Height, body weight (BW), ice hockey history as well as lean body mass (LBM)and and peak torque (PT) of the thigh muscles, VO 2peak and anaerobic performance (OBLA, RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 46 publications
7
33
0
Order By: Relevance
“…The strength of relationship seen between the results of the analysis of RER 1.05 and race performance are on par with those reported for other measures of the anaerobic threshold and performance (35). In particular the 2 recent studies that have examined RER in combination with athletic performance (1,10) reported moderate to strong correlations, similar to those seen in the present investigation. Although many of those comparisons were made with more controlled situations (i.e., road races or laboratory tests).…”
Section: Discussionsupporting
confidence: 85%
“…The strength of relationship seen between the results of the analysis of RER 1.05 and race performance are on par with those reported for other measures of the anaerobic threshold and performance (35). In particular the 2 recent studies that have examined RER in combination with athletic performance (1,10) reported moderate to strong correlations, similar to those seen in the present investigation. Although many of those comparisons were made with more controlled situations (i.e., road races or laboratory tests).…”
Section: Discussionsupporting
confidence: 85%
“…Research on female hockey, and particularly competitive-level female hockey, is somewhat limited 5. However, because of different biological, sociocultural, and financial preconditions, knowledge of male hockey cannot outright be applied on female hockey 7. Thus, while skating is considered the most important skill in ice hockey,8 factors that might best explain key performance characteristics of skating in competitive-level female ice hockey remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A personal daily logbook was given to each subject for recording exercise, to ensure training load within the given prescription and furthermore note if any health problem occurred during the study period. Aerobic performance was assessed with an incremental test on an electronically braked bicycle (Monark, 839 E, Sweden) with a metabolic gas measurement system (Meta Max II, CORTEX, Bio physic GmbH, Leipzig, Germany), method described in Gilenstam et al [20]. For each individual, the cycle ergo meter tests were identically performed at the two occasions, approximately at the same time of the day and with same technical assistance.…”
Section: Methodsmentioning
confidence: 99%